2021
DOI: 10.4018/ijer.20210101.oa2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Object Tracking Performance Between Professional and Amateur eSport Players as Well as Traditional Sportsmen

Abstract: High performance in multiple object tracking paradigms is associated with well-trained visuo-spatial abilities, visual memory and divided attention. These abilities are essential for both traditional sport and esport. The present study compared the tracking performance of professional as well as amateur esport players and traditional sportsmen. Professional esport players outperformed amateurs, while no other group differences were found. Positive association of esport playtime and tracking performance as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Similarly, three studies (Bickman et al, 2020(Bickman et al, , 2021Wechsler et al, 2021) found that pro-gamers perform better than non-professionals due to better hand-eye coordination, mental strength, response time, game knowledge, and tactical comprehension. However, Sousa et al (2020) observed that pro-gamers' faster response times are marred by less accuracy and impulsiveness.…”
Section: Physiology and Health Of Pro-gamersmentioning
confidence: 95%
“…Similarly, three studies (Bickman et al, 2020(Bickman et al, , 2021Wechsler et al, 2021) found that pro-gamers perform better than non-professionals due to better hand-eye coordination, mental strength, response time, game knowledge, and tactical comprehension. However, Sousa et al (2020) observed that pro-gamers' faster response times are marred by less accuracy and impulsiveness.…”
Section: Physiology and Health Of Pro-gamersmentioning
confidence: 95%
“…Sports scientists have studied the association between sports experience (expertise) and visual attention during the last decade, and those studies have yielded mixed results. A number of studies have demonstrated that expert athletes exhibit better visual attention performance than novice players ( Heppe et al, 2016 ; Voss et al, 2010 ; Wechsler et al, 2021 ). It has also been widely demonstrated that extensive sports training may improve cognitive function and may lead to plasticity changes in brain structure and function ( Etnier et al, 2006 ; Kramer & Erickson, 2007 ).…”
Section: Introductionmentioning
confidence: 99%